JMJD3 promotes the epithelial-mesenchymal transition and migration of glioma cells via the CXCL12/CXCR4 axis - Zou, Shuang (Oncol Lett, 2019)
Histone H3K27 demethylase Jumonji domain-containing protein 3 (JMJD3) is involved in somatic cell differentiation and tumor progression; however, the underlying mechanisms of JMJD3 in cancer progression are yet to be fully explored. To improve understanding regarding the function of JMJD3 in brain tumor cells, the present study investigated the effects of JMJD3 on the epithelial-mesenchymal transition (EMT) and migration in glioma cells, and the underlying mechanisms involving the C-X-C motif chemokine ligand 12 (CXCL12)/C-X-C motif chemokine receptor 4 (CXCR4) axis. Immunohistochemical staining of a tissue microarray of glioma samples confirmed that JMJD3 overexpression could stratify highly metastatic glioma. The overexpression of JMJD3 induced a spindle-shaped morphology, promoted N-cadherin expression, inhibited E-cadherin expression and enhanced the migration ability of U-251MG and U-87MG American Type Culture Collection cells. The expression of E-cadherin and N-cadherin were assessed by western blotting and reverse transcription-quantitative polymerase chain reaction, and cell migration was evaluated using a Transwell migration assay and wound-healing. The overexpression of JMJD3 upregulated CXCL12 expression in a demethylase activity-dependent manner as ChIP assays revealed a decrease in H3K27 trimethylation at the CXCL12 promoter following overexpression of JMJD3 in U-87MG ATCC cells. Accordingly, CXCL12 overexpression was sufficient to rescue the suppressive effects of JMJD3 inhibition on the EMT and migration in glioma cells. In addition, CXCR4 expression was not regulated by JMJD3, but the interruption of CXCR4 caused by the CXCR4 inhibitor AMD3100 abolished the promotional effect of JMJD3 on EMT and migration in glioma cells. Collectively, these results suggested that JMJD3 promoted EMT and migration in glioma cells via the CXCL12/CXCR4 axis. The present study described a novel epigenetic mechanism regulating tumor cell EMT and migration, and provided a novel direction for glioma diagnosis and treatment.